THE DEVELOPMENT OF PARLIAMENTARISM IS AN IMPORTANT FACTOR OF DEMOCRACY - Usmanova Umida Samatovna (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
This article discusses issues related to the development of a democratic society in the Republic of Uzbekistan.